Differences between suicide note leavers and other suicides: A German psychological autopsy study. (May 2021) - Lang, Anne; Brieger, Peter; Menzel, Susanne; Hamann, Johannes
Abstract: Introduction: Suicide notes are not only the last personal message from the suicide victim to the bereaved, but are also a valuable source for research in preventing suicides. However, not all suicide victims leave a suicide note and it is unclear whether note leavers are representative of the general population of suicide victims. Methods: The aim of our study was to compare suicide victims who leave a suicide note compared to those who do not. Therefore, data from the Allgäu Suicide Study, which comprised detailed information on N = 626 suicides, were analysed using multiple regression analyses. Results: Of N = 612 cases with complete data, n = 255(42%) left a suicide note and n = 357 (58%) did not. Persons who wrote suicide notes before they killed themselves were more often female, less often married, found themselves more often in a financial or partnership crisis, and were more likely to suffer from a medical illness. They tended to poison themselves more often and were less likely to have a history of alcohol abuse disorder. Conclusion: Suicide notes are one source to better understand the motives, which lie behind suicides and therefore may help to further develop and improve suicide prevention programs. Keeping in mind that suicide has heterogeneous reasons, the group of "note writers" might be one, which might especially have benefitted from psychosocial and psychotherapeutic interventions, as interpersonal relationships obviously played an important role even shortly before suicide.